2003
DOI: 10.1001/archopht.121.6.821
|View full text |Cite
|
Sign up to set email alerts
|

Axial Length–Disc Area Ratio in Esotropic Amblyopia

Abstract: Background: Hyperopia is a risk factor for esotropia and amblyopia. A previous study indicated that disc areas (DAs) are reduced in patients with amblyopia. Objective: To determine if there is a difference in the relative size of the optic disc in hyperopic eyes without strabismus or amblyopia compared with esotropic and amblyopic eyes, the relationship of axial length (AXL) to DA in subjects with hyperopia was evaluated. Methods: Eight hundred fifty records from my private practice, which included AXL measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…Although most studies state the single cause and effect relationship noted above, several laboratory and clinical studies have made additional observations beyond the standard explanation (Almeder et al, 1990; Barrett et al, 2005; Lempert, 2000, 2003, 2004, 2008b; Lempert and Porter, 1998). In one instance the question has been cast as an interesting case of “which came first, the chicken or egg?” (Fielder and Moseley, 1996).…”
Section: Cause and Effect: A Classic Chicken And Egg Storymentioning
confidence: 99%
See 1 more Smart Citation
“…Although most studies state the single cause and effect relationship noted above, several laboratory and clinical studies have made additional observations beyond the standard explanation (Almeder et al, 1990; Barrett et al, 2005; Lempert, 2000, 2003, 2004, 2008b; Lempert and Porter, 1998). In one instance the question has been cast as an interesting case of “which came first, the chicken or egg?” (Fielder and Moseley, 1996).…”
Section: Cause and Effect: A Classic Chicken And Egg Storymentioning
confidence: 99%
“…However, definitive evidence that anisometropia universally precedes development of the amblyopia is lacking, and the simplicity of this cause and effect relationship continues to be challenged (Almeder et al, 1990; Barrett et al, 2005; Lempert, 2000, 2003, 2004, 2008a, 2008b; Lempert and Porter, 1998, Smith and Hung, 1999). In light of the general uncertainty about the aetiology of anisometropia and anisometropic amblyopia, an examination of the literature is timely as part of the continuing effort to refine approaches to vision screening and clinical care.…”
Section: Introduction and Rationalementioning
confidence: 99%
“…They concluded that unilateral amblyopia was associated with bilaterality, but also with subclinically hypoplastic ONs, greater than normal AL/ ON, and abnormal noncircular globe cross-section. Lempert [4,19] studied photographs of the ONs of human eyes with amblyopia and found that the optic disks of hypermetropic eyes with strabismus (with and without amblyopia) were disproportionately small in size compared with hypermetropic eyes without amblyopia or esotropia. He speculated that vision impairment in amblyopia is associated with ON hypoplasia with relative microphthalmos.…”
Section: Discussionmentioning
confidence: 99%
“…In special, esotropia is the most common cause of strabis mic and combined (strabismic and anisometropic) amblyopia (6,7) . Previous studies reported that esotropic amblyopic eyes are shorter than their fellow eyes (8,9) . Although most researchers agree that refractive error is in large part genetically determined, a growing body of evidence shows that visual experiences early in life may influence ocular growth and eventual refractive status (10) .…”
Section: Introductionmentioning
confidence: 91%
“…Eyes with amblyopia represent a group in which there is an abnormal visual input and this could be associated with impaired modulation of axial growth. Most previous investigations on amblyopic eyes (8,9,11) concentrated solely on the total axial length, not on the contribution of each ocular component to the total axial length. Only one study evaluated the contribution of anterior chamber depth, lens thickness and vitreous chamber depth as percentages of axial length in strabismic amblyopes.…”
Section: Biometric Relationships Of Ocular Components In Esotropic Ammentioning
confidence: 99%